Integrative Analysis of Methylation and Copy Number Variations of Prostate Adenocarcinoma Based on Weighted Gene Co-expression Network Analysis - Hou, Yaxin; Hu, Junyi; Zhou, Lijie; Liu, Lilong; Chen, Ke; Yang, Xiong (Frontiers in Oncology, 2021)
As the most pervasive carcinoma diagnosed in males with a total number exceeds 170000 new cases every year in America, prostate adenocarcinoma (PRAD) causing the second death number among all cancer types in men despite its indolent course. Prostate-specific antigen (PSA) testing, the most commonly used non-invasive inspection method of PRAD which has improved detection rate significantly in the past decade, but the function on evaluating progress and prognosis of PRAD remains controversial. To seek novel efficient biomarkers, we took advantage of the TCGA database, using Weighted Gene Co-expression Network Analysis (WGCNA) to handle the top 10000 largest variant genes and gain the clinical associated modules. Methylation and copy number variation analysis were then carried out to screen obviously aberrant genes, after which Kaplan-Meier analysis and Gene Set Enrichment Analysis (GSEA) were respectively used for evaluating the prognosis and potential mechanism of genes in PRAD. Our research revealed that CCNE2, RHPN1, EZH2, TONSL, EPHX2 are all potential prognostic indicators for PRAD patients, FMOD and SLC7A4 are possible novel biomarkers as well as therapeutic targets for PRAD.